De novo SOX6 variant: Tolchin-Le Caignec syndrome - Sinha, Rahul; Singh, Sonali; Kamila, Gautam (International Journal of Contemporary Pediatrics, 2022)
Tolchin-Le Caignec syndrome (TOLCAS) is a developmental disorder characterized by intellectual impairment and behavioural issues such as autism, hyperactivity, aggressive episodes and mood swings and lack of sleep. The other manifestations include osteochondroma, craniosynostosis, dysmorphic facies, arachnodactyly, prominent occiput and bitemporal narrowing. We reported this rare syndrome in a 5 and half year old female child who presented with global developmental delay (language and cognitive predominant), autistic features, hyperactivity, aggressive behaviour and dysmorphism (high forehead, bitemporal narrowing, micrognathia, low set ears, hypertelorism, wide nasal bridge, scaphocephaly, clinodactyly). The whole exome sequencing detected de novo heterozygous missense pathogenic variant c.1378A>C, p. (Asn460His) in exon 11 of SOX6 gene with no similar variant found in either of the parents confirmed the diagnosis of TOLCAS. This rare case report highlighted the phenotypic variation due to SOX6 gene mutation which the clinician should be aware of while dealing with dysmorphic child with cognitive and language delay with autistic features.